Cultura organizacional, inovação e gestão ambiental: integrando conceitos para a edificação de organizações sustentáveis - Jabbour, Charbel José Chiappetta; Oliveira, Sônia Valle Walter Borges de; Castro, Rosani de [UNESP] (My University, 2011)
The main purpose of this article is to relate two among the most important themes of the current organizational dynamic: organizational culture, innovation and environmental management. Great part of the literature about environmental management and environmental innovation refers to organizational culture as the most arduous wall or the most significant element to develop effective practices of business environmental management. However, relationship among such concepts is, many times, superficial or camouflaging the necessary analytic depth. To solve this challenge, this article integrates the levels of the organizational culture (workmanships, values and presupposed unconscious), the typologies of environmental innovation (total productivity of resources, innovations for the segregation of materials and articulation of bio-systems), and the environmental technologies (end-of-pipe, environmental measurement, pollution prevention and zero-impact technology). Recommendations and challenges for the continuity of this research are registered.

O objetivo deste artigo é relacionar alguns dentre os mais importantes temas do atual contexto organizacional: cultura organizacional, inovação e gestão ambiental. Grande parte da literatura que versa sobre gestão ambiental e sobre inovação ambiental atribui à cultura organizacional a mais árdua barreira ou o mais significativo dos facilitadores para que uma organização desenvolva práticas efetivas de gestão ambiental. Entretanto, relacionamento entre tais conceitos é, muitas vezes, tratado de forma superficial ou camuflando-se a densidade analítica necessária para se refletir de forma integrada sobre cultura organizacional e inovações ambientais. Para fazer frente a esse desafio, este artigo integra os níveis da cultura organizacional (artefatos, valores e pressupostos inconscientes) às tipologias de inovação ambiental (produtividade total de recursos, inovações para a segregação de materiais e articulação de bio-sistemas) e às tecnologias orientadas à gestão ambiental (final-de-processo, mensuração ambiental, prevenção da poluição e tecnologia isenta de impactos). Recomendações e desafios para a continuidade da linha de pesquisa são registrados.
Organizational culture, innovation and environmental management: integrating concepts to build sustainable organizations
Keywords: Organizational culture; Environmental administration; Environmental innovation; Technologies environmental; Cultura organizacional; Gestão ambiental; Inovação ambiental; Tecnologias ambientais